Review of Islamic Law on Giving Rewards to Users of the Snack Video Application in the City of Pare-Pare - serliani, Serliani (Program Studi Hukum Ekonomi Syariah, Institut Agama Islam Negeri Parepare, 2023)
Review of Islamic Law on Giving Rewards to Snack Video Application Users in Parepare City. From the results of this study it was found that the application of the ujrah contract related to giving rewards to video snack application users in the city of Parepare, is fully in accordance with the concept of the ujrah contract where there is a job carried out by snack video users by completing missions given such as inviting friends, doing check-in every day, follow and like videos of other users and become content creators, so that users are entitled to get rewards after the work is completed, but according to a review of Islamic law the income from watching videos and the wages earned by ating content contains elements of gharar, namely ambiguity in it and can cause makruh even the heart causes the income generated to become illegitimate, because there are activities that can damage maqashid sharia in the daruriyyat element, namely hifdz al-mal, preserving assets from things that can make them haraam, and also on the mission of watching videos it is not known how many a definite amount, because every time you complete a mission the reward coins you get are different, this is not in accordance with the concept of pillars and conditions of ujrah, namely wages must be stated clearly. Meanwhile, the mission of inviting friends using referrals is included in the pure contract of giving from the video snack company.